Microstation of digital processing of biomedical images. - Corkidi Blanco, Gabriel; Márquez Flores, Jorge (Revista Mexicana de Ingenieria Biomedica, 1991)
The elements and applications of a microstation of digital image processing in biomedicine are described. For a better understanding, the context in which said system intervenes is explained.